2009
DOI: 10.1002/adma.200801492
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Porous Carbon Materials with Designed Pore Architecture

Abstract: Recent progress in syntheses of porous carbons with designed pore architecture has rejuvenated the field of carbon chemistry and promises to provide new advanced materials. In order to reap the full benefit of designer carbons, it is necessary to develop chemistries for functionalizing the porous carbon surfaces. This Review examines methods of functionalizing porous carbon through direct incorporation of heteroatoms in the carbon synthesis, surface oxidation and activation, halogenation, sulfonation, grafting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
506
0
13

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 838 publications
(525 citation statements)
references
References 263 publications
(412 reference statements)
6
506
0
13
Order By: Relevance
“…[9] Porous carbonaceous materials are traditionally prepared by physical activation, chemical activation, or by a combination of the two. [10] Highly porous carbons have been produced in the past with the use of KOH as a chemical activating agent, through precursors including linear polymers, [11,12] carbon nanotubes, [13] and graphene oxide.…”
Section: Doi: 101002/adma201603051mentioning
confidence: 99%
“…[9] Porous carbonaceous materials are traditionally prepared by physical activation, chemical activation, or by a combination of the two. [10] Highly porous carbons have been produced in the past with the use of KOH as a chemical activating agent, through precursors including linear polymers, [11,12] carbon nanotubes, [13] and graphene oxide.…”
Section: Doi: 101002/adma201603051mentioning
confidence: 99%
“…The relative contributions of the surface functional groups were evaluated by deconvolution of the C 1s, O 1s, and N 1s core elements level are provided in Figure 3. The assignments of the different surface groups were made according to the literature [36,37] and based on the position of the chemicals shifts in the core elements level; further details are provided in Table S1 in the supplementary information file. Note that for the pristine samples prepared without carbon black, the majority of carbon element is in C-C configuration, and about 38-40 % in oxidized forms, with very little variation upon the incorporation of the carbon black additive or the activation post-treatment.…”
Section: Structural Characterization Of the Aerogels And Chemical Anamentioning
confidence: 99%
“…In general, carbon materials with high specific surface areas and a large number of narrow micropores have a higher capability for charge accumulation at the electrode/electrolyte interface [6,7]. In addition, capacitance performance can be improved by the incorporation of certain types of heteroatoms such as nitrogen into the carbon framework [3,8]. Indeed, it has been reported that Ndoped porous carbons clearly exhibit a superior performance as supercapacitors due to an enhancement of their electronic conductivity and surface wettability in addition to the pseudo-capacitive effects contributed by the nitrogen functional groups [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%